Copy number gain of MYCN gene is a recurrent genetic aberration and favorable prognostic factor in Chinese pediatric neuroblastoma patients - Wang Miao; Zhou Chunju; Cai Rongqin; Li Yong; Gong Liping (BMC, 2013)
Abstract Background Amplification of MYCN oncogene is an established marker indicating aggressive tumor progression of neuroblastoma (NBL). But copy number analyses of MYCN gene in ganglioneuroblastoma (GNBL) and ganglioneuroma(GN) is poorly described in the literature. In the study, we evaluated the copy number aberrations of MYCN gene in clinical samples of NBLs, GNBLs and GNs and analyzed their association with clinical outcome of the patients. Methods In this study, we analyzed MYCN gene and chromosome 2 aneusomy by using fluorescence in situ hybridization (FISH) method in a total of 220 patients with NBL, GNBL and GN cases. Kaplan-Meier curves were generated by using SPSS 12.0 software. Results Of 220 patients, 178 (81.0%) were NBLs, 32 (14.5%) were GNBLs and 10 (4.5%) were GNs. MYCN gain is a recurrent genetic aberration of neuroblastic tumors (71.8%, 158/220), which was found in 129 NBLs (58.6%, 129/220), 25 GNBLs (11.4%, 25/220) and 4 GN cases (1.8%, 4/220). However, MYCN amplification was only present in 24 NBL tumors (13.5%, 24/178) and 1 GNBL case (3.1%, 1/32). Kaplan-Meier survival analysis indicated that MYCN amplification is significantly correlated with decreased overall survival in NBLs (P=0.017). Furthermore, a better prognosis trend was observed in patients with MYCN gain tumors compared with those with MYCN gene normal copy number tumors and MYCN amplification tumors (P=0.012). Conclusions In summary, the frequency of MYCN amplification in NBLs is high and is rarely observed in GNBLs and GNs, which suggest MYCN plays an important role in neuroblastic tumors differentiation. MYCN gain appeared to define a subgroup of NBLs with much better outcome and classification of MYCN gene copy number alteration as three groups (amplification, gain and normal) can provide a powerful prognostic indicator in NBLs. Virtual Slides The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/6417541528559124